Optimization of Tilt Angle for Photovoltaic: Case Study Sabang-Indonesia. Issue 1 (June 2019) - Yassir, A; Zamzami, U; Fauzan, K; Hasannuddin, T; Subhan,
Abstract: Renewable energy sources as alternative energy are needed for electrical power, reliability such as Sabang tourism area. This paper provides the most optimal angle of installation of photovoltaic (PV) to obtain the optimum PV energy with the genetic algorithm method. Daily energy that PV can accept as fitness, the tilt angle (β) as an individual evaluation with a limit of -90o to 90o. The optimal tilt angle in the area of the simulation results is equal to 6o facing south. Comparisons are made with tilt angles of 15, 30, and 60 facing south. The results show that installation with an optimal angle with the genetic algorithm method can increase the energy received by PV by 2%, 9.5%, and 38%.